Global Research Trends in Complementary and Alternative Therapies for Primary Dysmenorrhea Among Adolescent Girls: A Bibliometric Analysis - Ririn Indriani; Salma Santi Widuri (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Primary dysmenorrhea is highly prevalent among adolescent girls and often leads to significant functional impairment. Growing interest in complementary and alternative therapies (CAM) reflects a shift toward safer, accessible non-pharmacological options. However, research in this field remains fragmented, and no bibliometric analysis has mapped its global structure. This study aimed to analyze global research trends, scholarly productivity, collaborative networks, and emerging thematic structures related to complementary and alternative therapies for primary dysmenorrhea among adolescent girls. A bibliometric analysis was conducted using PubMed-indexed publications from 2019–2024. Eligible English-language articles were analyzed using Biblioshiny (R Studio) to assess publication trends, key contributors, collaboration networks, and thematic evolution. A total of 293 documents from 171 journals were included, showing an annual growth rate of 9.86%. Research involved 2003 authors, with high collaboration rates and strong contributions from China, the United States, and the Netherlands. Thematic mapping identified movement-based therapeutic approaches particularly walking and functional recovery as dominant motor themes, reflecting emerging interest in physiological and rehabilitative dimensions of dysmenorrhea management. Research on CAM for primary dysmenorrhea among adolescents has expanded rapidly, with increasing global collaboration and evolving thematic complexity. Movement-based interventions and functional recovery frameworks represent key future directions, offering promising avenues for developing holistic and adolescent-centered menstrual pain management strategies.